Collecting and preserving the Ukraine conflict (2014-2015): a web archive at University of California, Berkeley. Issue 3 (4th July 2016) - Pendse, Liladhar R.
Abstract : Purpose: The purpose of this paper is to highlight the web-archiving as a tool for possible collection development in a research level academic library. The paper highlights the web-archiving project that dealt with the contemporary Ukraine conflict. Currently, as the conflict in Ukraine drags on, the need for collecting and preserving the information from various web-based resources with different ideological orientations acquires a special importance. The demise of the Soviet Union in 1991 and the emergence of independent republics were heralded by some as a peaceful transition to the "free-market" style economies. This transition was nevertheless nuanced and not seamless. Besides the incomplete market liberalization, rent-seeking behaviors of different sort, it was also accompanied by the almost ubiquitous use of and access to the internet and the internet communication technologies. Now 24 years later, the ongoing conflict in Ukraine also appears to be unfolding on the World Wide Web. With the Russian annexation of Crimea and its unification to the Russian Federation, the governmental and non-governmental websites of the Ukrainian Crimea suddenly came to represent a sort of "an endangered archive". Design/methodology/approach: The main purpose of this project was to make the information that is contained in Ukrainian and Russia websites available to the wider body of scholars and students over the longer period of time in a web archive. The author does not take any ideological stance on the legal status of Crimea or on the ongoing conflict in Ukraine. There are currently several projects that are devoted to the preservation of these websites. This article also focuses on providing a survey of the landscape of these projects and highlights the ongoing web-archiving project that is entitled, "the Ukraine Crisis: 2014-2015" at the UC Berkeley Library. Findings: The UC Berkeley's Ukraine Conflict Archive was made available to public in March of 2015 after enough materials were archived. The initial purpose of the archive was to selectively harvest, and archive those websites that are bound to either disappear or change significantly during the evolution of Crimea's accession to Russia. However, in the aftermath of the Crimean conflict, the ensuing of military conflict in Ukraine had forced to reevaluate the web-archiving strategy. The project was never envisioned to be a competing project to the Ukraine Conflict project. Instead, it was supposed to capture complimentary data that could have been missed by other similar projects. This web archive has been made public to provide a glimpse of what was happening and what is happening in Ukraine. Research limitations/implications: Now 24 years later, the ongoing conflict in Ukraine also appears to be unfolding on the World Wide Web. With the Russian annexation of Crimea and its unification to the Russian Federation, the governmental and non-governmental websites of the Ukrainian Crimea suddenly came to represent a sort of "an endangered archive". The impetus for archiving the selected Ukrainian websites came as a result of the changing geopolitical realities of Crimea. The daily changes to the websites and also loss of information that is contained within them is one of the many problems faced by the users of these websites. In some cases, the likelihood of these websites is relatively high. This in turn was followed by the author's desire to preserve the information about the daily lives in Ukraine's east in light of the unfolding violent armed conflict. Originality/value: Upon close survey of the Library and Information Sciences currently published articles on Ukraine Conflict, no articles that are currently dedicated to archiving the Crimean and Ukrainian situations were found.